Collaboration as a service (CaaS) to fully integrate public transportation – Lessons from long distance travel to reimagine mobility as a service. (January 2020) - Merkert, Rico; Bushell, James; Beck, Matthew J.
Highlights: We introduce the concept of Collaboration as a Service (CaaS), an extension of MaaS. We provide lessons from the macro sector to better integrate the micro transport sector. Airline style cooperation may be a template for cooperation in public transport. We outline the potential for alliances and networks as a coordinative body. Smart ticketing systems can form the technological basis to facilitate CaaS. Abstract: Integrated mobility aims to improve multimodal integration to make public transport an attractive alternative to private transport. This paper critically reviews extant literature and current public transport governance frameworks of transport operators across a macro and micro spectrum. Our aim is to extend the concept of Mobility-as-a-Service (MaaS), a proposed coordination mechanism for public transport that is yet to prove its commercial viability and general acceptance. Drawing from avaition experiences, we propose that smart ticketing systems, providing Software-as-a-Service (SaaS) can be extended with governance and operational processes that enhance their ability to facilitate Collaboration-as-a-Service (CaaS) to offer a reimagined MaaS2.0 = CaaS + SaaS. Rather than using the traditional MaaS broker, CaaS incorporates operators more fully and utilises their commercial self-interest to deliver commercially viable and attractive integrated public transport solutions to consumers. This would also facilitate more collaboration of private sector operators into public transport across short and long distance with potentially new opportunities for taxi/rideshare/bikeshare operators and cross geographical transport providers (i.e. transnational multimodal operating companies) to integrate.